The old quantum theory - Haar, D. ter (Commonwealth and international library. Selected readings in physics., 1967)
The Old Quantum Theory explains how the classical laws were modified by Planck, Einstein, Rutherford, Bohr, and other contributors to account for atomic phenomena, comprising the development of quantum theory from its start at the very end of the 19th century until the beginning of the 20th century. This book begins by discussing Planck's discovery of his radiation law, followed by Einstein's introduction to quanta. Next is a description of the Rutherford model of the atom and Bohr's postulates, which are confirmed by the Franck-Hertz experiment. This selection concludes with a description of how Bohr's theory could explain the main features of the atomic spectra. A brief summary of other important developments in the period are also elaborated. This publication is beneficial to students and researchers conducting work on the history of quantum mechanics from the 1900s to the development of wave mechanics.